State‐of‐play for cellular therapies in cardiac repair and regeneration. (27th August 2021) - Vaka, Ramana; Davis, Darryl R.
Abstract: Cardiovascular disease is the primary cause of death around the world. For almost two decades, cell therapy has been proposed as a solution for heart disease. In this article, we report on the "state‐of‐play" of cellular therapies for cardiac repair and regeneration. We outline the progression of new ideas from the preclinical literature to ongoing clinical trials. Recent data supporting the mechanics and mechanisms of myogenic and paracrine therapies are evaluated in the context of long‐term cardiac engraftment. This discussion informs on promising new approaches to indicate future avenues for the field. Abstract : Cardiovascular disease is the primary cause of death around the world. For almost two decades, cell therapy has been proposed as a solution for heart disease. In this article, we report on the "state‐of‐play" of cellular therapies for cardiac repair and regeneration.